2002
DOI: 10.1007/s10052-002-0976-0
|View full text |Cite
|
Sign up to set email alerts
|

The cosmological evolution of the nucleon mass and the electroweak coupling constants

Abstract: Starting from astrophysical indications that the fine structure constant might undergo a small cosmological time shift, we discuss the implications of such an effect from the point of view of particle physics. Grand unification implies small time shifts for the nucleon mass, the magnetic moment of the nucleon and the weak coupling constant as well. The relative change of the nucleon mass is about 40 times larger than the relative change of α. Laboratory measurements using very advanced methods in quantum optic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
218
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(222 citation statements)
references
References 12 publications
2
218
1
1
Order By: Relevance
“…Due to its large vapor pressure and small polarisability, it is straightforward to produce an intense beam of CO molecules. Using pulsed laser light around 206 or 199 nm, the spin forbidden a 3 …”
Section: A Proposed Experiments In Metastable Comentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its large vapor pressure and small polarisability, it is straightforward to produce an intense beam of CO molecules. Using pulsed laser light around 206 or 199 nm, the spin forbidden a 3 …”
Section: A Proposed Experiments In Metastable Comentioning
confidence: 99%
“…Possible variations can be detected from a wide variety of physical phenomena, but the extreme accuracy that can be obtained in the determination of frequencies or wavelengths of spectral lines in atoms and molecules makes spectroscopy the ideal testing ground for searches of varying a and m. 2 The proton-electron mass ratio is of particular interest as theoretical models predict that the variation of m could be significantly larger than the variation of a. Calmet and Fritsch, for instance, predict that the variation of m is 38 times larger than the variation of a. 3 Recent astrophysical data suggest that the fine structure constant, a, has increased over cosmological time. The combined analysis over more than 100 quasar systems has produced a value of a relative change of Da/a ¼ À0.57 AE 0.10 Â 10 À5 , which is at the 5s significance level.…”
Section: Introductionmentioning
confidence: 99%
“…The relation between a time-varying fine structure constant and other observables in particle physics was also treated in [11,12,13]. In [11] the resulting variation in the vacuum energy V 0 was estimated from general principles of QFT and found to be enormously larger than the cosmological bounds; hence, the authors concluded that a large number of implausibly accurate fine-tunings would be necessary for a time variation of the size that has been claimed to be consistent with field theory and cosmology.…”
Section: Relation To Recent Workmentioning
confidence: 99%
“…Calmet and Fritszch [12] calculate some of the consequences for low-energy physics of changing α, within a GUT-like theory which constrains the SM gauge couplings to be equal at a particular energy scale (or at least to satisfy some fixed relation). They consider exclusively the effects on the strong interactions, with the unstated assumption that the mechanisms of electroweak symmetry-breaking, supersymmetry-breaking and fermion mass generation are held constant despite varying the unified coupling, hence that the quark and lepton masses, as well as W and Z masses, remain unchanged.…”
Section: Relation To Recent Workmentioning
confidence: 99%
See 1 more Smart Citation